The First Missionaries of The Church Missionary Society in Sierra Leone, 1804–1816: A Biographical Approach. (22nd May 2017) - Keefer, Katrina H.B.
Abstract: Many early records in West Africa arise from missionary accounts. While they may contain rich ethnographic data, this detail should be approached only after analysis and consideration of the authors of the sources in question. In early Sierra Leone, important data was recorded on behalf of the English evangelical Church Missionary Society, but the missionaries reporting on the ground comprised an insufficiently studied group of German-speaking Pietist Lutherans originating from central and northern Europe. This article analyzes the authors of this information in order to approach their accounts with a better appreciation of existing bias and to better engage with how diverse sociocultural perspectives affect the historical record. Résumé: En Afrique de l'Ouest, les écrits des missionnaires figurent parmi les premières sources disponibles sur l'histoire de la région. Bien que ces textes puissent contenir de riches données ethnographiques, les détails qu'ils fournissent ne doivent être abordés qu'après analyse et prise en compte des auteurs des sources en question. Au début de l'histoire de la Sierra Leone, des données importantes ont été mises par écrit au nom de la Church Missionary Society évangélique anglaise, mais parmi les missionnaires travaillant sur place se trouvait aussi un groupe insuffisamment étudié de luthériens piétistes germanophones originaires d'Europe centrale et du Nord. Cet article analyse les auteurs de ces informations afin d'aborder leurs écrits ainsi que leur biais de manière critique et afin de mieux approcher la manière dont diverses perspectives socioculturelles affectent les sources historiques.